Local Adaptation of Work Practices: The Case of BancoEstado’s “CajaVecina” Correspondent Banking System - Juan Felipe Espinosa-Cristia; José Ignacio Alarcón; Bernardo Batiz-Lazo (SAGE Open, 2022)
This article contributes to the discussion of everyday domestic finance technologies by looking at CajaVecina, a correspondent banking network coordinated by BancoEstado, a leading Chilean financial institution. Differences in perceptions between actual users and designers of ICT for development projects (ICT2D) emerged from structured interviews with executives of financial intermediaries, customers, and shopkeepers. The extent to which independent merchants operating CajaVecina’s bespoke terminals confront and solve the “design-actuality gap” questioned whether the CajaVecina system enabled neighborhood retail stores to act as a de facto bank branch. Empirical results suggested that was not the case. Instead of following strict contractual behavior, participants in the correspondent banking network addressed a design gap through social interaction and leveraging relationships with repeat customers. This behavior builds on information emanating from what they called “operating quotas.” Operating quotas enabled BancoEstado to diversify risk, document financial services habits, and forecast the performance of merchants (particularly small, independent retail shops). Merchants used trends in operating quotas to tailor services offered through the CajaVecina terminal while aiming to increase the loyalty of trusted customers. These results further the understanding of correspondent banking services aiming to increase financial inclusion by providing evidence of a previously unexplored aspect of these networks, where social dimensions take precedence over economic, financial, and technological aspects.